Something Old, Something New, Something Borrowed: The Alt-Right on Building Christendom Without Christ - Shaw, Daniel Odin (Journal for the study of religions and ideologies, 2019)
The rise of the Alt-Right has changed the face of the American and international far-right. Although an online movement, it has shown a growing influence on political discourse. One puzzling and understudied aspect of this movement is its relationship to religion. Stanchly anti-Muslim and heavily reliant on Christian identity and iconography, it is nevertheless made-up of a significant number of avowed atheists. A desire to protect Christendom from outside influences is combined with a focus on rationalism and anti-Christianity drawn from the writings of the new atheists. This paper will combine preliminary content analysis of online comments with an examination of prominent alt-right YouTube videos in order to understand the role of these competing ideological strands within the movement. YouTube has become a particularly fertile group for the Alt-Right, with many prominent commentators achieving popularity on the site. Crucially, these mediums allow for the candid observation of deliberation on religious and ideological issues between members of the Alt-Right. This methodology will allow for an understanding of how this group perceives and constructs its own relationship to religion, rather than simply how it presents itself. This paper will therefore seek to make a contribution which is both theoretical and methodological.